Production of advanced materials by methods of self-propagating high-temperature synthesis - Tavadze, Giorgi F. (SpringerBriefs in Materials, 2013)
This translation from the original Russian book outlines the production of a variety of materials by methods of self-propagating high-temperature synthesis (SHS). The types of materials discussed include: hard, refractory, corrosion and wear-resistant materials, as well as other advanced and speciality materials. The authors address the issue of optimal parameters for SHS reactions occurring during processes involving a preliminary metallothermic reduction stage, and they calculate this using thermodynamic approaches. In order to confirm the effectiveness of this approach, the authors describe experiments focussing on the synthesis of elemental crysalline boron, boron carbides and nitrides. Other parts of this brief include theoretical and experimental results on single-stage production of hard alloys on the basis of titanium and zirconium borides, as well as macrokinetics of degassing and compaciton of SHS-products.This brief is suitable for academics, as well as those working in industrial manufacturing companies producing hard alloys and composites for making metal-working machinery or drilling equipment.